Adalimumab treatment leads to reduction of tissue tumor necrosis factor‐alpha correlated with venous leg ulcer improvement: a pilot study. Issue 5 (24th September 2015) - Fox, Joshua D; Baquerizo‐Nole, Katherine L; Keegan, Brian R; Macquhae, Flor; Escandon, Julia; Espinosa, Aliette; Perez, Carmen; Romanelli, Paolo; Kirsner, Robert S
Abstract: Venous leg ulcers (VLUs) have higher tumor necrosis factor‐α (TNF‐α) levels compared with normal skin. Refractory VLUs of long duration have higher TNF‐α levels compared with VLUs of shorter duration. As up to 75% of VLUs fail to heal with standard care, we sought to evaluate the role of anti‐TNF‐α therapy for patients with refractory VLUs. Evaluable data were obtained in four of five subjects with recalcitrant VLUs treated with 80 mg of subcutaneous adalimumab at week 0 and with 40 mg at week 2 along with compression therapy and were followed‐up for 6 weeks. Wound biopsies taken at weeks 0 and 4 were stained with anti‐TNF‐α antibodies. Average 4‐week percent wound size reduction was 20.5% ± 6.4%. Two patients had wound size reduction more than 25%, and their percent wound size reduction correlated to percent TNF‐α staining score reductions ( P = 0.02, R 2 = 0.999). VLU TNF‐α level decrease 4 weeks post‐adalimumab treatment correlated with wound healing.